Electric machines : steady-state theory and dynamic performance - Sarma, Mulukutla S., 1938- (Minneapolis/St. Paul : West, 1994)
This book is divided into three parts: Introduction; Steady-State theory and performance; Transients and dynamics.
Keywords: Electric machinery; Electric machinery